The common drivers of default risk - Christoph Memmel; Yalin Gündüz; Peter Raupach (Deutsche Bundesbank, 2012)
Using a unique data set on German banks' loans to the German real economy, we investigate banks' credit risk. This data set includes the volume of loans per bank and industry as well as the corresponding write-downs. Our empirical study for the period 2003-2011 yields the following results: (i) Beyond the nationwide credit loss rate, industry composition, and regional factors, the loans' maturity structure is found to drive the bank-wide loss rates in the credit portfolio. (ii) The nationwide loss rate has the most impact, followed by the maturity structure and the industry composition. (iii) For nationwide banks, these common factors explain about 26% of the time variation in the loss rate of credit portfolios; for regional banks, this percentage is less than eight percent.
Keywords: G21; 330; credit risk; systematic risk; maturity; stress tests